ByzRev 06.2024.004: Marek Meško, Alexios Komnenos in the Balkans, 1081–1095: (New Approaches to Byzantine History and Culture). Cham: Palgrave MacMillan 2023. - Kyriakidis, Savvas (The Byzantine Review, 2024)
Marek Meško, Alexios Komnenos in the Balkans, 1081–1095 (New Approaches to Byzantine History and Culture). Cham: Palgrave MacMillan 2023. xvi + 425 pp. – ISBN 978-3-031-26295-1